Culeolus antarcticus Vinogradova 1962 - Sanamyan, K. E.; Sanamyan, N. P. (Zenodo, 2002)
Culeolus antarcticus Vinogradova, 1962 (®gure 24) Culeolus antarcticus Vinogradova, 1962b: 207; Monniot and Monniot, 1982: 117; 1985b: 31. Culeolus sluiteri : Diehl, 1977: 147. Material examined . St. 896, 5651±5530 m, one specimen; st. 925, 2980±2960 m, one specimen; st. 908, 5474±5465 m, one specimen; st. 916, 4664±5631 m, ®ve specimens. Description . The body length is from 10 to 36 mm and all the specimens have broken peduncles. The general body shape is similar in all specimens, the body being elongate and slightly tapering anteriorly. The thin and ®rm test is completely covered by small spherules. A few of these slightly protrude like small papillae, but in a 30 mm specimen from st. 925, the papillae are longer and more numerous, giving the specimen a shaggy appearance. The postero-ventral crest is T-shaped (®gure 24A), it consists of a short mid-ventral branch and two lateral branches running obliquely from the most postero-ventral point of the body and ending some distance from the corners of the slit-like atrial aperture. The lateral branches are straight or their free ends slightly curved dorsally and posteriorly (but not ventrally as ®gured by Vinogradova, 1962b). The mid-ventral branch is absent only in the smallest (10 mm) specimen. The postero-ventral crest has sometimes free papillae, or they are united along most of their length to form a solid lamella. Papillae are arranged in one line in most specimens, but are crowded and form a wide band in the`shaggy’ specimen referred above. About 22 large and heavily branched tentacles are present. In opened specimens they hide the whole prebranchial area and project beyond the rim of the branchial siphon. The branchial sac has usually six folds on each side, but only ®ve on the right side in the 30 mm specimen from st. 908. The branchial formula of the ®gured specimen is: E2(3)2(4)2 (6)4 (7)3(7)4 (4)2DL3(5)5 (4)3(6)3(5)2 (3)1(4)2E. One gonad is present on each side of the body, the left is in the gut loop. Each gonad consists of three to seven lobes; the ...